2007
DOI: 10.1210/jc.2007-1253
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Gene Markers and Insights into the Pathophysiology of Pheochromocytoma Malignancy

Abstract: The gene expression profiling of benign and malignant pheochromocytomas clearly identified a set of genes that could be used as a prognostic multi-marker and revealed that the expression of several genes encoding neuroendocrine proteins was reduced in malignant compared with benign tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
1
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 18 publications
5
45
1
1
Order By: Relevance
“…Brouwers et al 38 examined 20 malignant tumors along with 70 sporadic and syndromic benign tumors: Gene Ontology Analysis of benign and malignant tumor comparison revealed the relevance of signal transduction changes. The significant gene sets established in two recent large-scale studies by Thouënnon et al 39 and Suh et al 40 are quite different, which indicates the need for further, large-scale gene expression profiling studies.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Brouwers et al 38 examined 20 malignant tumors along with 70 sporadic and syndromic benign tumors: Gene Ontology Analysis of benign and malignant tumor comparison revealed the relevance of signal transduction changes. The significant gene sets established in two recent large-scale studies by Thouënnon et al 39 and Suh et al 40 are quite different, which indicates the need for further, large-scale gene expression profiling studies.…”
Section: Discussionmentioning
confidence: 96%
“…Transcriptomic studies representing targets of miRNA-based regulation are pivotal for the correct interpretation of miRNA findings. There have been six previous studies 11,[37][38][39][40][41] on gene expression profiling involving malignant pheochromocytomas to date. The studies of Dahia et al, 11 Björklund et al 37 and the most recent study of Waldmann et al 41 included only two, three and five malignant pheochromocytomas, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of expression of members of this family of proteins has been observed in a number of tumour types, including QPCT itself in melanoma (Muthusamy et al, 2006) and phaeochromocytomas (Thoue¨nnon et al, 2007). SCUBE (Signal peptide CUB EGF-like domain-containing protein) genes encode a small group of secreted plasma membrane-associated proteins characterised by an N-terminal signal peptide sequence, multiple EGF (epidermal growth factor) domains, a large spacer region containing multiple N-linked glycosylation sites and a C-terminal CUB (Complement subcomponent C1r/C1s EGF-related sea Urchin protein, Bone morphogenetic protein1) domain (Grimmond et al, 2000).…”
Section: Ct Bstu1mentioning
confidence: 99%
“…In a previous study, we have shown the differential expression in benign versus malignant pheochromocytomas of peptidylglycine a-amidating monooxygenase (PAM), the enzyme responsible for the amidation and therefore the stability as well as the activity of PACAP, NPY, and AM (Thouennon et al 2007), suggesting a potential alteration of the function of these amidated peptides. Because these peptides exert proliferative and/or anti-apoptotic effects on various cell types, positively regulate catecholamine secretion from chromaffin cells in physiological or pathophysiological conditions, and can be linked to angiogenesis which represents an important feature of tumorigenesis, especially in tumors exhibiting high vascularization such as pheochromocytomas, we carried out in the present study a systematic quantitative survey of the expression of these trophic peptides and their receptors in benign and malignant pheochromocytomas.…”
Section: Introductionmentioning
confidence: 99%